Like Father Like Sons? The Cost of Sovereign Defaults in Reduced Credit to the Private Sector. Issue 7 (15th September 2016) - ESTEVES, RUI; TOVAR JALLES, JOÃO
Abstract : We investigate the impact of sovereign defaults on the ability of the corporate sector in emerging nations to finance itself abroad. We test the hypothesis that sovereign defaults have a negative spillover onto the private sector through credit rationing. We explore a novel data set covering the majority of corporates in emerging nations that received foreign capital between 1880 and 1913. Results confirm that credit rationing existed, was very large, and persisted long beyond the default settlement. The private sector paid a severe cost for their governments' debt intolerance, with negative implications for their growth.